Implementation of Halal Certification for Micro, Small, And Medium Enterprises In West Tulang Bawang District - Febrimayanti Febrimayanti (Administrative and Environmental Law Review, 2020)
Companies that want to do business that involve the food sector (restaurants, catering, slaughterhouses and home industry) are required to obtain halal certification permits. In order to determine business lines, whether micro, large, medium, small businesses are based on the initial asset value, this does not include the appraisal value of land and buildings and turnover from the total sales of goods or the number of permanent employees. Based on the results of the research, the requirements for granting halal certificates are KTP (Identity Card) of Business Owners, Business Permits, IUMK (Micro and Small Business Permits), Home Industry Food (P-IRT), and NPWP (Taxpayer Identification Number). Whereas the procedure has an understanding regarding the requirements for halal certification and is willing to take part in the halal assurance system training, implement the Halal Assurance system (SJH), prepare halal certification document files, carry out (upload halal certification data document), monitor pre-inspection and make certification accent payments, carry out inspection, conducts post-inspection monitoring, has Halal Certification. Thus, the requirements and procedures for granting Halal Certification, especially in West Tulang Bawang Regency, can be done easily. It's just that it requires extra power and maximum effort to obtain this. Thus, it is necessary to provide convenience and relief in the cost of making Halal Certificates, especially for the general public, whose majority still lack knowledge of technology.